2021
DOI: 10.1155/2021/4471117
|View full text |Cite
|
Sign up to set email alerts
|

A Robust MP3 Steganographic Method against Multiple Compressions Based on Modified Discrete Cosine Transform

Abstract: MP3 appears in various social networking sites wildly, and it is very suitable to be applied for covert communication indeed. However, almost all social networking sites recompress the uploaded MP3 files, which leads to the ineffectiveness of the existing MP3 steganographic methods. In this paper, a robust MP3 steganographic algorithm is proposed with the ability of multiple compressions resistance. First, we discover a new embedding domain with strong robustness. The scalefactor bands of higher energy are app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Two more features that the user can control and affect the size and quality are the sampling rate, which is determined by the MPEG-1 protocol at 32 kHz, 44.1 kHz and 48 kHz [12], and the channel mode, with four supported choices: monophonic mode, stereo mode, dual-monophonic mode (identical to stereo mode) and joint stereo mode [13]. Some studies have suggested improvements on the MP3 algorithm, in terms of encryption [14], prevention of multiple compression [15], improved over-the-Internet transmission [16] and also for improving the quality of low bitrate files [17].…”
Section: Introductionmentioning
confidence: 99%
“…Two more features that the user can control and affect the size and quality are the sampling rate, which is determined by the MPEG-1 protocol at 32 kHz, 44.1 kHz and 48 kHz [12], and the channel mode, with four supported choices: monophonic mode, stereo mode, dual-monophonic mode (identical to stereo mode) and joint stereo mode [13]. Some studies have suggested improvements on the MP3 algorithm, in terms of encryption [14], prevention of multiple compression [15], improved over-the-Internet transmission [16] and also for improving the quality of low bitrate files [17].…”
Section: Introductionmentioning
confidence: 99%